Leptonic Modeling of the Multiwavelength Spectra of Astrophysical Sources - Palomino Ylla, Ariadna Uxue (2021)
This work is motivated by the physical processes which take place in active galactic nuclei (AGN). They are powerful sources of radiation in a wide wavelength. To gain knowledge about these processes, multiwavelength spectral energy distributions (SED) are used. The current work uses three types of distributions applied to two blazars, a variety of AGN objects. The SED of blazars typically has a double-hump structure which can be explained in terms of two models: the hadronic and the leptonic model. A model built only by leptonic processes (in this case, inverse Compton and synchrotron) has proved to be fairly-good to explain the gamma-ray emission from most blazars. The Python package Naima restricts model parameters to find the best fit for the observed data and characterize the source by proposing processes that could take place there. The SEDs of the Mrk 421 and PKS 0537-441 blazars were modelled. The best fits obtained follows an electron differential distribution of the form of an exponential cutoff power law. They have a reduced c2 of 1.92 and 2.58, respectively. For the fitted model for the blazar PKS 0537-441, the radiation of the flux of photons product of the synchrotron process produces the major contribution on the inverse Compton flux.